Progress for tolerance to inbreeding in some tropical maize populations. - Vasal, S. K.; Vergara, N.; McLean, S. (Agronomía Mesoamericana, 2016)
Considering interest in line and hybrid development in recent years, CIMMYT initiated a modest hybrid development effort in in 1985. Among the various activities of the hybrid program, the development of hybridoriented germplansm source with increaseed inbreeding tolerance was regarded as an important activity. In this study nine tropical poplatíons were improved for inbreeding tolerance using S3 recurrent selection. The performance of S1 bulk and full vigor F2 seed from C0, C1 and C2 was compared to evaluate progress at 3 sites in 1991-92 using split-plot design with 4 replications. The yield of SI bulk relative to F2 was used as a measure to evaluate progress for inbreeding tolerance. Among the 9 tropical populations, the population 21 exibited a yield gain of 18% followed by population 23 (10.9%). The yicld gains measured in S1 bulks werc much higher. The maximun gains occurred in Popo 23 (31.8%), Pop. 26 (30.8%) and Pop. 21 (24.0(;70). All populations exhibited gains, however, popo 26 registered a gain of 65.4% in C2 in comparison to 45% in C0. The populations 27 and 36 expressed a high level of tolerance to inbreeding in C2 (78%). In general, yield gains were associated with s!ight increments in plant height and later maturity.